Maintenance of University Facilities in Developing Country: Case study of Lagos State University Ojo Nigeria - Oyenuga, S.O.; Akinsola, O. E.; Hussaini, P. O.; Fatokun, A.O. (Richtmann Publishing, 2012)
Cursory study of universities in developing countries has been a subject of concern. This necessitated a study into themaintenance of Lagos state university Ojo Campus Nigeria with a view to identify certain factors responsible for the deterioratingstate of the facilities and also proffer remedial solution to the problems. The research used both qualitative and quantitativemethod. Group focus and in-depth interview are some of the many formal approaches that are used. These include; customerfeedback forms, report or media clip. Data are collected using sampling techniques and structured questionnaire, incorporating afixed set and order of questions with a closed list of responses. Out of the Twenty-Two (22) questionnaire sent, only seventeen(17) were responded to, representing a seventy-seven (77%) response rate. The data collected were analyzed using descriptiveand inferential statistics. The study revealed that; lack of planned maintenance, lack of maintenance policies in the institution,lack of update security system and qualified personnel are among the major factor influencing deteriorating state of facilities atthe university. The research work concludes that lack of planning approach to maintenance issue and structured maintenancepolicy is the banes of the university facilities problem.The study also conclude that there are no regular inspections of thefacilities to check maintenance needs and the university does not use facilities to generate fund, other than government fundingfor maintenance purposes. The paper recommends that universities in developing countries should have a good maintenancepolicy in place and use facilities for investment purposes to foster increased income to cater for maintenance needs among otherthings.